Antiproliferative Effects of Selected Chemotherapeutics in Human Ovarian Cancer Cell Line A2780 - Kateřina Caltová; Miroslav Červinka (Acta Medica, 2012)
The aim of our study was to determine the effect of selected cytostatics on a human ovarian cancer cell line A2780 as a model system for ovarian cancer treatment. This cell line is considered cisplatin-sensitive. Panel of tested cytostatics included cisplatin, paclitaxel, carboplatin, gemcitabine, topotecan and etoposide. These cytostatics have a different mechanism of action. To evaluate cytotoxic potential of the tested compounds, the methods measuring various toxicological endpoints were employed including morphological studies, MTT assay, dynamic monitoring of cell proliferation with xCELLigence, cell cycle analysis, caspase 3 activity and expression of proteins involved in cell cycle regulation and cell death. The A270 cell line showed different sensitivity towards the selected cytostatics, the highest cytotoxic effect was associated with paclitaxel and topotecan.